Rare Tree Species Pattern Diversity in Two Virgin Jungle Reserves in Pahang and Johor, Malaysia (ID 572-531) - Hikmat, Agus; Mohammad, Abdul Latiff; Ibrahim, Faridah Hanum; Jusoff, Kamaruzaman (2007)
A study on the distribution pattern of rare tree species was carried out in Bukit Bauk Virgin Jungle Reserve (VJR), Terengganu and Gunung Pulai VJR, Johor. A single plot of 2 ha (100 m x 200 m) was established in each VJR by using purposive sampling design. The plot was further divided into contiguous 50 subplots of 20 x 20 m2. Based on the IUCN categories, six species are critically endangered and two species vulnerable in Bukit Bauk VJR. In Gunung Pulai, five species each are critically endangered and vulnerable. Both VJRs registered tree species distribution that is random and clumped in different proportions.